Endometrial carcinoma: Evaluation using diffusion‐tensor imaging and its correlation with histopathologic findings. Issue 1 (19th November 2018) - Yamada, Ichiro; Wakana, Kimio; Kobayashi, Daisuke; Miyasaka, Naoyuki; Oshima, Noriko; Wakabayashi, Akira; Saida, Yukihisa; Tateishi, Ukihide; Eishi, Yoshinobu
Abstract : Background: Although the prognosis of endometrial carcinoma (EMC) patients strictly depends on tumor invasion depth and its histologic grade, accurate preoperative assessment of these prognostic factors is often difficult. Purpose: To determine the usefulness of diffusion‐tensor imaging (DTI) as a noninvasive method for evaluating tumor invasion depth and its histologic grade in patients with EMC. Study Type: Prospective. Population: Twenty‐five consecutive patients with histologically confirmed EMC who were surgically treated at our institution. Field Strength/Sequence: DTI was performed with a 1.5T MRI system using a single‐shot echo‐planar imaging sequence with b values of 0 and 1000 s/mm 2 and motion‐probing gradients in nine noncollinear directions. Assessment: Fractional anisotropy (FA), mean diffusivity (MD), and axial diffusivity (AD) maps were analyzed by three observers and compared with histopathologic findings. Statistical Tests: Dunnett's test, Spearman's rank correlation coefficient, and receiver operating characteristic (ROC) curve analyses. Results: FA maps from all patients distinctly identified the junctional zone as a high‐FA zone (0.864 ± 0.037) that was significantly different from the endometrium and outer myometrium (0.251 ± 0.030 and 0.471 ± 0.091, respectively; P  < 0.001). All EMCs were clearly depicted as hypointense areas on all DTI maps. AD maps provided the best tumor‐to‐uterus contrast, and EMCs (0.977 ± 0.120 × 10 −3 mm 2 /s) had significantly lower AD values than all other layers of the normal uterine wall (2.166 ± 0.408, 2.010 ± 0.289, and 2.655 ± 0.203 × 10 −3 mm 2 /s, respectively; P  < 0.001). EMCs were clearly demarcated from the normal uterine wall, and DTI maps and histopathologic data yielded identical findings regarding tumor invasion depth. FA values showed a significant inverse correlation ( r  = –0.818; P  < 0.001) with histologic grades 1, 2, and 3 of endometrioid adenocarcinomas. Data Conclusion: In patients with EMC, DTI may be useful for evaluating tumor invasion depth and its histologic grade. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:250–260.